Development of an Indirect ELISA Kit for Rapid Detection of Varicella-Zoster Virus Antibody by Glycoprotein E - Niu, Yan; Wang, Aiping; Zhou, Jingming; Liu, Hongliang; Chen, Yumei; Ding, Peiyang; Qi, Yanhua; Liang, Chao; Zhu, Xifang; Zhang, Gaiping (Frontiers in Microbiology, 2022)
Varicella-zoster virus (VZV), a highly infectious agent that causes varicella (chickenpox), can also cause zoster (shingles), a disorder that is frequently associated with severe neuralgia. A reliable serological VZV diagnostic assay would be useful for identifying unprotected individuals and for surveilling post-vaccination immunoprotection status. Toward this goal, VZV membrane glycoprotein E (gE), the immunodominant VZV protein, served as target antigen in an indirect ELISA kit developed here to detect anti-VZV antibodies in clinical samples. For target antigen preparation, Chinese hamster ovary (CHO) cells were modified to express and secrete the VZV gE ectodomain, which was subsequently purified and used as coating antigen in an indirect ELISA. Ultimately, the optimal purified gE coating antigen concentration was determined to be 2 μg.ml-1 and the OD450 nm detection cut-off value was 0.286. The coefficient of variation (CV) of intra-assay and inter-assay were < 10 % and 15 %, respectively. A comparative test of 66 clinical samples showed that the coincidence rate was 93.9 % between the indirect ELISA and a commercial varicella-zoster virus IgG ELISA kit. Thus, the indirect ELISA kit developed here may be useful for achieving rapid, sensitive and specific detection of anti-VZV antibodies.